Frontal cortical thickness correlates positively with impulsivity in early psychosis male patients. Issue 4 (17th May 2018) - Baumann, Philipp S.; Klauser, Paul; Griffa, Alessandra; Golay, Philippe; Palix, Julie; Alameda, Luis; Moulin, Valérie; Hagmann, Patric; Do, Kim Q.; Conus, Philippe
Abstract : Aim: Impulsive behaviours, which are frequent in young people suffering from psychosis have been linked to risky and violent behaviours and participate to the burden of psychotic illness. Given that morphological brain correlates of impulsivity in schizophrenia have been poorly investigated especially in young adults, the aim of this study was to investigate the relationship between impulsivity and cortical thickness in early psychosis (EP) patients. Method: A total of 17 male subjects in the early phase of psychosis were recruited. Impulsivity was assessed with the Lecrubier Impulsivity Rating Scale. Mean cortical thickness was extracted from magnetic resonance imaging brain scans, using surface‐based methods. Results: Mean cortical thickness in the frontal lobe correlated positively with mean impulsivity in EP male patients. Conclusion: Our results suggest that psychotic subjects exhibiting higher impulsivity have larger frontal cortical thickness, which may pave the way towards the identification of patients with a higher risk to display impulsive behaviours.